Disinfection of water using chlorine generated on-site by the electrolysis of sodium chloride (common salt) - Ofosu-Boateng, Samuel Kwabena (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of the Degree of Master of Science in Water Supply and Environmental Sanitation,